Peningkatan Proses Dan Hasil Belajar IPAS Menggunakan Model Role Playing - Yuni Zikra Arahmah (CV. Master Literasi Indonesia, 2026)
This research is motivated by the lack of engagement and collaboration between students, leading to a tendency for students to be less active and quickly become bored. Therefore, a learning model that can improve student learning processes and outcomes is the Role-Playing model. The purpose of this study was to determine the effectiveness of the Role-Playing model in improving learning processes and outcomes in fifth-grade science subjects at SDN 27/II Sungai Arang. This study was a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects were 20 fifth-grade students at SDN 27/II Sungai Arang. Data collection techniques included observation, testing, and documentation. Data collection instruments used observation sheets from educators and students, along with test questions, were then compiled through qualitative and quantitative data analysis techniques. The results of the study demonstrate the learning processes and outcomes of fifth-grade science subjects at SDN 27/II Sungai Arang. The detailed results of educator observations in Cycle I were 78%, categorized as good, and in Cycle II, 90.5%, categorized as very good. Student observations in Cycle I were 50%, categorized as poor, and in Cycle II, 97.5%, categorized as very good. Student learning outcomes in Cycle I were 65%, categorized as sufficient, and in Cycle II, 86%, categorized as very good. It was concluded that the use of the Role-Playing model can improve the process and outcomes of social studies learning.